2022
DOI: 10.1063/5.0097279
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly frequency-tuneable, in-vacuum, and magnetic levitation chopper for fast modulation of infrared light

Abstract: We present an in-vacuum mechanical chopper running at high speed and integrated into a magnetic levitating motor for modulating optical beams up to 200 kHz. The compact chopper rotor allows fast acceleration (10 kHz s−1 as standard) for rapid tuning of the modulation frequency, while 1 mm diameter slots provide high optical throughput for larger infrared beams. The modulation performances are assessed using a reference visible laser and the high brightness, broadband, infrared (IR) beam of synchrotron radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Therefore, we have first proposed and patented [17] a configuration of chopper disk with non-linear margins, outward or inward oriented. We have demonstrated that such devices, in their simpler configuration, with semi-circular margins of the windows do allow for a more flexible design of the profile of the generated laser impulses [16,18], as a supplemental degree-of-freedom (DOF) is added to the analysis and design process, i.e. the radius ρ of the semi-circular margins.…”
Section: Choppers With Shafts Vs Choppers With Disksmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we have first proposed and patented [17] a configuration of chopper disk with non-linear margins, outward or inward oriented. We have demonstrated that such devices, in their simpler configuration, with semi-circular margins of the windows do allow for a more flexible design of the profile of the generated laser impulses [16,18], as a supplemental degree-of-freedom (DOF) is added to the analysis and design process, i.e. the radius ρ of the semi-circular margins.…”
Section: Choppers With Shafts Vs Choppers With Disksmentioning
confidence: 99%
“…Choppers with rotational elements are one of the most utilized optomechanical modulators [1], together with optical scanners of different types [2][3][4][5][6]. Most common choppers are built with rotational disks [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], but we have introduced, patented [25], and developed [26][27][28][29][30] a novel type of choppers, with rotational shafts of different shapes (for example cylindrical, conical, or spherical), with slits of different profiles (i.e., with linear margins or as cylindrical holes). Such devices have the potential of surpassing the well-known 10 kHz limit of the chop frequency fc of choppers with disks.…”
Section: Introductionmentioning
confidence: 99%
“…To utilize broadband IR light emitters, which are cost-effective, external modulation or chopping of the optical beam is necessary to achieve the desired modulation depth and frequency. Various types of optical beam choppers have been reported in the literature, including mechanical choppers, microelectromechanical systems (MEMS) choppers or in-vacuum choppers. However, mechanical choppers are bulky systems with a limited frequency modulation range of ∼10 kHz, while infrared lasers with built-in pulsing circuits are expensive as well as bulky . Therefore, these IR modulation platforms are not suitable for applications in portable and miniaturized systems, especially together with a broad-wavelength source of IR light.…”
Section: Introductionmentioning
confidence: 99%